Nieliberalna koncepcja praw podstawowych Carla Schmitta - Merkwa, Marcin (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2025)
The purpose of this article is to show the concept of fundamental rights as formulated by Carl Schmitt in two works: Constitutional Theory and Legality and Legitimacy. The first part outlines Schmitt's critique of liberalism as an ideology that cannot serve as a basis for a strong state. The next section points out the inconsistencies Schmitt perceived in the Weimar Constitution. The third part presents the concept of fundamental rights as grounded in Schmitt's interpretation of the Weimar Constitution. The lawyer's critique of legal positivism and liberalism resulted, in the field of fundamental rights, in the articulation of a concept seen by scholars both as a defence of liberal values, but also as a negation of the modern idea of inalienable individual rights. Regardless of its assessment, it represents an interesting and still valid attempt to define the relationship between the individual and the state.
Keywords: fundamental rights; constitution; liberalism; Carl Schmitt